On-line coupling of derivatization with pre-concentration to determine trace levels of methotrexate - Samy Emara; Tsutomu Masujima; Walaa Zarad; Maha Kamal; Ramzia EL-Bagary (Elsevier, 2013)
A new simple, sensitive and precise green analytical procedure using an automated packed-reactor derivatization technique coupled with on-line solid-phase enrichment (SPEn) has been developed and evaluated to determine trace levels of methotrexate (MTX). The method was based on injection of MTX into a flowing stream of phosphate buffer (0.04Â M, pH 3.4), carried through the packed oxidant reactor of Cerium (IV) trihydroxyhydroperoxide for oxidative cleavage of the drug into highly fluorescent product, 2,4-diaminopteridine-6-carboxylic acid, followed by SPEn on a head of short ODS column (10Â mmÃ4.6Â mm i.d., 5Â Î¼m particle size). The flow rate was 0.25Â mL/min and packed reactor temperature was 40Â Â°C. The trapped product was back-flush eluted from the ODS column to the detector by column-switching with an environmentally friendly mobile phase consisting of ethanol and phosphate buffer (0.04Â M, pH 3.4) in the ratio of 5:95 (v/v). The eluent was monitored at emission and excitation wavelengths of 460 and 360Â nm, respectively. The calibration curve was linear over the concentration range of 1.25â50Â ng/mL with a detection limit of 0.08Â ng/mL. The method was successfully applied to determine MTX in pharmaceutical formulations with mean percentage recovery ranging from 99.48 to 99.60. Keywords: Methotrexate, Flow injection analysis, Cerium (IV) trihydroxyhydroperoxide, On-line solid-phase enrichment, Fluorescence detection